Assessment Of Investment Strategy With A Utility-Based Approach - Nuryana, Ida (Publisher Cv. Inara, 2022)
The purpose of this study is to analyze the assessment of investment strategies with a utility-based approach. The rise of investment at this time has the aim of increasing welfare in the present and in the future. Investing is expected to have the best investment strategy and be supported by investment knowledge. Investment strategy requires consideration of economic factors, business intuition, experience. Approaching retirement age, investments are made more determined by psychological factors, therefore, it is necessary to manage the financial portfolio of retirement income with the right strategy. How to manage investments in a retirement portfolio. People who have entered retirement age always want to get the maximum utility from the pension money they have earned so far. When money has been invested in certain assets, under which conditions are formed: (1) the safest investment withdrawal rate (2) can be used in the possibility of running out of money which is considered to have failed to plan as the main measure of investment performance in a pension fund portfolio.